Interactions of polyvinylpyrrolidone with imidazolium based ionic liquids: Spectroscopic and Density Functional Theory studies - Bahadur, I.; Ebenso, E.E.; Seru-Katata, L.M. (Elsevier, 2016)
A polyvinylpyrrolidone (PVP) polymer has been shown to interact with the ionic liquids (ILs), 1-butyl-3-methylimidazolium bis(trifluromethylsulfonyl)imide [BMIM][Tf2N], 1-butyl-3-methylimidazolium methylsulphate [BMIM][MeSO4], and 1-ethyl-3-methylimidazolium-n-octylsulphate [EMIM][OS]. Ultraviolet-visible spectroscopy (UV-Vis), Fourier transform infrared spectroscopy (FT-IR) and confocal Raman spectroscopy have revealed that these ILs have the ability to interact with the polymer. The Density Functional Theory (DFT) calculation has been performed to optimize the ILs-PVP systems. The results show that there are several H-bonds between ILs and PVP. This study delivers the mutual effect of the polymer and ILs that may create many theoretical and experimental opportunities.
Keywords: Ionic liquid; Polymer; UV; Raman; FT-IR spectroscopy; Density Functional Theory (DFT)